Art District in Puerto Vallarta: diversification of the tourist offers. - Zepeda Arce, Alfonso (2023)
Various cities around the world are examples of how art (Bilbao, London) and in particular the creative districts (Miami, Mexico City) have been dynamic agents and promoters of tourism development, which have strengthened and created new business opportunities. Puerto Vallarta, a tourist city in the state of Jalisco, the center and motor of development of the area, a destination for the coastline of traditional unplanned development that has made tourism the base of its economy, is a mature destination that requires diversification and new revitalizing agents of the tourism. The objective of this work is to display the territorial conceptualization that defines the main characteristics of the Puerto Vallarta Art District, based on a sociodemographic and economic analysis of the downtown area of ​​the city, which would provide a new life by diversifying the existing cultural offer. and becoming a complementary alternative to the traditional offer of sun and sand. Some of the conclusions are that it is observed that there is a permanent construction of a creative economy in the art district of Puerto Vallarta. However, there is a lack of a municipal, state and federal government policy to support the consolidation of these creative companies, becoming a weakness.